2010
DOI: 10.1007/s11883-010-0145-0
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Red Yeast Rice for the Physician

Abstract: Red yeast rice is an ancient Chinese dietary staple and medication used by millions of patients as an alternative therapy for hypercholesterolemia. In recent years, the use of red yeast rice has grown exponentially due to increased public interest in complementary and alternative medications and the publication of several randomized, controlled trials demonstrating its efficacy and safety in different populations. The most promising role for red yeast rice is as an alternative lipidlowering therapy for patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 54 publications
(44 reference statements)
0
22
0
Order By: Relevance
“…Red yeast rice has been shown to have significant cholesterol lowering properties [77] however issues over standardized manufacturing practices have been limiting factors to wider promotion [78]. The varying preparations are also an issue when comparing studies of the efficacy of red yeast rice [79]. …”
Section: Lifestyle Modification or Non Pharmacological Management Of mentioning
confidence: 99%
“…Red yeast rice has been shown to have significant cholesterol lowering properties [77] however issues over standardized manufacturing practices have been limiting factors to wider promotion [78]. The varying preparations are also an issue when comparing studies of the efficacy of red yeast rice [79]. …”
Section: Lifestyle Modification or Non Pharmacological Management Of mentioning
confidence: 99%
“…Isolated via fermentation of red yeast (Monascus purpureus), on rice, red yeast rice has been cited for its "digestion and circulation" benefits as early as 800 ad during the Tang dynasty in China. 33 This supplement's current popularity is largely driven by numerous studies that have headlined its potent lipidlowering effect. The fermentation process used to culture red yeast rice produces 14 monacolins, which are understood to be inhibitors of hydroxymethylglutaryl-coenzyme A (HMG-CoA) reductase, which is responsible for cholesterol synthesis.…”
Section: Red Yeast Ricementioning
confidence: 99%
“…Merck & Co. marketed this particular monacolin under the trade name MevacorÔ in 1987, establishing the first Food and Drug Administration(FDA)-approved line of HMG-CoA reductase inhibitors. 33 Although monacolin is found ubiquitously in red yeast rice, a 2010 study by Gordon et al found marked variability of monacolin concentrations in 12 OTC formulations, including monacolin K. 34 Manufacturers of these supplements each claimed that they contained 600 mg of red yeast rice. The findings, based on third-party laboratory analyses, detected monacolin K levels ranging variably from 0.10 to 10.09 mg per 600-mg capsule.…”
Section: Red Yeast Ricementioning
confidence: 99%
“…This rice derivative is used as a traditional Chinese food and a dietary additive against hypertension, altered lipidemia and glycemia, and osteoporosis (Dong and Cai 2011). Red yeast rice is frequently used by patients with intolerance for standard anticholesterolemic drugs like statins (Gordon and Becker 2011;Musselman, Pettit et al 2012). The active principles of red yeast rice include a class M A N U S C R I P T…”
Section: Hypercholesterolemia and Cardiovascular Diseasementioning
confidence: 99%
“…Moreover, red yeast rice production can affect the formation of unwanted compounds, particularly the nephrotoxic citrinin (Childress, Gay et al 2013). Hence, physicians and patients should be cautious in recommending or adopting this alternative therapy for hyperlipidemia (Gordon and Becker 2011).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%